1977
DOI: 10.1111/j.1745-6584.1977.tb03191.x
|View full text |Cite
|
Sign up to set email alerts
|

Cleat Orientation and Areal Hydraulic Anisotropy of a Wyoming Coal Aquifer

Abstract: The anisotropic, areal hydraulic conductivity of the Felix No. 2 coal (Eocene, Wasatch Formation) has been defined in a four‐well pump test at a site in the Powder River Basin of northeastern Wyoming. The direction of maximum hydraulic conductivity of the subbituminous coal bed bears N59°E and is associated with a horizontal hydraulic conductivity of 0.27 m/day. The direction of minimum hydraulic conductivity bears N31°W and is associated with a horizontal hydraulic conductivity of 0.15 m/day. The direction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Previous tests (Stone and Snoeberger, 1977;Dobson, 1996) indicate that the maximum transmissivity is aligned nearly parallel to the face cleat orientation. For example, Stone and Snoeberger (1977) determined that maximum transmissivity was oriented N598E, and face cleats about N708E.…”
Section: Comparison Of Results To Other Testsmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous tests (Stone and Snoeberger, 1977;Dobson, 1996) indicate that the maximum transmissivity is aligned nearly parallel to the face cleat orientation. For example, Stone and Snoeberger (1977) determined that maximum transmissivity was oriented N598E, and face cleats about N708E.…”
Section: Comparison Of Results To Other Testsmentioning
confidence: 94%
“…Previous tests (Stone and Snoeberger, 1977;Dobson, 1996) indicate that the maximum transmissivity is aligned nearly parallel to the face cleat orientation. For example, Stone and Snoeberger (1977) determined that maximum transmissivity was oriented N598E, and face cleats about N708E. Results of the current test are of interest, in that they show the major transmissivity tensor axis to be oriented about 558 E of the face cleat orientation of N338, but nearly parallel to the strike of a major fracture orientation in the coals and interbedded sediments that may arise from a shift in the orientation of the stress field through geologic time (Morin, this issue).…”
Section: Comparison Of Results To Other Testsmentioning
confidence: 94%
See 1 more Smart Citation
“…Hydraulic properties of western coal seams are reported by McCord and others (1992) in Colorado and New Mexico and by others (1978, 1980), Chadwick (1981), Stoner (1981), and Stone and Snoeberger (1977) in low-rank beds of the Fort Union Formation in North Dakota, Montana, and Wyoming.…”
Section: Previous Investigationsmentioning
confidence: 71%
“…Schubert's (1980) summary of several studies indicated a range of 2 to 10 in West Virginia coals. Stoner (1981), Vogwill (1979), Stone and Snoeberger (1977), and Erickson (1970) found anisotropic ratios of western coals to differ by a factor of 2.5 and 2.9, 2.4, 1.8, and 4.8, respectively.…”
Section: Previous Investigationsmentioning
confidence: 97%